1973
DOI: 10.1182/blood.v42.4.611.611
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytosis Induced in Mice by Supernatant Fluids of Bordetella pertussis Cultures: A Histopathological Study

Abstract: Intravenous injection into mice of phase I Bordetella pertussis culture supernatants produces a marked lymphocytosis. The evolution of lymphocytosis was correlated with histopathological alterations in the lymphoid organs. The early phase, 17 hr to day 3, was associated with massive depletion of both lymphocytes from the white pulp of the spleen and of cortical thymocytes. There was a corresponding profound decrease of splenic and thymic weights. The later phase was associated with a marked decrease in lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…We also showed that SF alone has no mitogenic effect on mouse spleen cells (47). This was measured by [3H]thymidine incoroporation and by failure to induce cytotoxicity for 5 Crlabeled target cells. In contrast, SF does stimulate certain T cell responses: (i) [3H]thymidine incorporation in response to suboptimal doses of PHA was increased by previous or simultaneous in vitro exposure of spleen cells to SF, and (ii) in the mixed lymphocyte culture reaction, parental B1O.A spleen cells from SF-injected mice responded 10 times as vigorously to F1 hybrid cell as normal B1O.A spleen cells.…”
Section: Microbial Agentsmentioning
confidence: 72%
See 1 more Smart Citation
“…We also showed that SF alone has no mitogenic effect on mouse spleen cells (47). This was measured by [3H]thymidine incoroporation and by failure to induce cytotoxicity for 5 Crlabeled target cells. In contrast, SF does stimulate certain T cell responses: (i) [3H]thymidine incorporation in response to suboptimal doses of PHA was increased by previous or simultaneous in vitro exposure of spleen cells to SF, and (ii) in the mixed lymphocyte culture reaction, parental B1O.A spleen cells from SF-injected mice responded 10 times as vigorously to F1 hybrid cell as normal B1O.A spleen cells.…”
Section: Microbial Agentsmentioning
confidence: 72%
“…Evidence was subsequently presented that pertussis induces a change in the surface of lymphocytes which causes a decreased capacity to emigrate from the blood. Thus, lymphocytosis primarily reflects the inability of lymphocytes to recirculate via post capillary venules into the lymphoid tissue (5,106).…”
Section: Cholera Enterotoxinmentioning
confidence: 99%
“…In the mouse, 3 ϫ 10 8 cells were collected during 48 h of thoracic duct cannulation with only small numbers of cells in lymph after this point (31). In mice treated with pertussis toxin, lymphocyte counts increased from 1.5 ϫ 10 7 to 1 ϫ 10 8 cells/ml of blood (1). Assuming that each 20-g mouse contains a total blood volume of 2 ml, the recirculating lymphocyte population measured after pertussis toxin injection was approximately 2 ϫ 10 8 lymphocytes.…”
mentioning
confidence: 99%
“…which is due primarily to a redistribution of small lymphocytes and is associated with depletion and repopulation of lymphoid organs of both T-and B-lymphocytes (1,15,17). Further-more, we have shown previously that the depopulation and repopulation of small lymphocytes of the spleen and lymph nodes do not occur in a synchronous manner (1).…”
Section: Resultsmentioning
confidence: 97%